Development of solar cell experiment for junior high school: investigating the effect of wavelength on current and voltage - Rabah Wahidin, Naufal; Cahya Prima, Eka; Riandi (Research in Physics Education, 2023)
Laboratory activities have the potential to enhance engagement through observation, experimentation, and active involvement. This study focuses on developing a solar cell experiment for junior high school students. The procedures involve measuring the dominant wavelength across various visible light spectrum and exploring the relationship between wavelength and the voltage and current output from a solar cell. The results indicate a negative correlation between wavelength and voltage/current. The highest recorded voltage and current, 1.75 V and 13.9 μA, respectively, were obtained at a wavelength of 400 nm. In contrast, the light with the highest wavelength, 650 nm, yielded the lowest recorded voltage and current, which were 1.43 V and 8.7 μA. Such laboratory activities can serve as valuable tools for teachers to impart the concept of wavelength and its real-world applications to students without the need for expensive or advance tools.